Problems of production and using of briquetted metal discard - N. A. Svidunovich; L. Z. Pisarenko; D. V. Kuis; Ju. P. Bobrov (Литьë и металлургия)
There is given the general information about development of metal discard recycling by means of briquetting, using bindings and deoxidizers.